Anterior Syndesmotic Augmentation Technique Using Nonabsorbable Suture-Tape for Acute and Chronic Syndesmotic Instability. (October 2020) - Kwon, John Y.; Stenquist, Derek; Ye, Michael; Williams, Caroline; Giza, Eric; Kadakia, Anish R.; Kreulen, Christopher
Syndesmotic instability is a source of significant pain and disability. Both subtle instability and gross diastasis, whether acute or chronic, require stabilization and may benefit from reconstruction with ligamentous augmentation. The use of nonabsorbable suture-tape has emerged as a promising operative strategy, allowing surgeons to anatomically reconstruct the syndesmosis, in particular the anterior inferior tibiofibular ligament. The current work provides a detailed description of the technique and preliminary results of a patient cohort treated using nonabsorbable suture-tape for syndesmotic augmentation. Level of Evidence: Level V, expert opinion.